ISOLATION OF OIL EATING FUNGI FROM PETROLEUM CONTAMINATED AREAS OF THE THAR DESERT - NISHI MATHUR; ANIL VYAS (International Journal of Pharma and Bio Sciences, 2016)
In present study, soil samples were collected from petroleum contaminated areas of the Thar Desert for the isolation of oil eating fungi. Initial assessment of the oil degrading fungi was done using mineral salt medium (MSM) supplemented with crude oil as the sole carbon source. Fungal counts were obtained from each of the samples and a total of seven fungal isolates were chosen. Their ability of utilizing crude oil was detected using vapor-phase transfer assay. Isolate F2 showed the maximum growth whereas isolate F7 showed the minimum growth. After morphologically identifying the fungal strains their viability assay was done using Fluorescence diacetate FDA hydrolysis Assay. Maximum viability of the mycelia was observed for strain F2, followed by F4 and F5 respectively, in the form of fluorescence under UV radiations